Enhancing Denture Success: A case report on prosthodontic rehabilitation of compromised maxillary and mandibular residual ridge - Maharjan, Susmita; Basnet, Bishal Babu; Parajuli, Prakash Kumar; Suwal, Pramita (Journal of Nepalese Prosthodontic Society, 2025)
Compromised residual ridges in edentulous elderly patients are common clinical finding with flabby tissue and atrophic ridges being the most common. Prosthetic rehabilitation of such ridges using conventional techniques may lead to failure of prosthesis. To achieve favorable prognosis, the rehabilitation begins with specialized impression technique. The window impression technique is used for flabby anterior maxillary ridge which records tissue in mucostatic state. The admix technique and neutral zone concept used for atrophic mandibular ridges allow physiologically optimal teeth arrangement enhancing stability thereby favoring prognosis of denture. With ongoing resorption, there is increase in restorative space between ridges resulting in increase in height and weight of prosthesis. This further overloads the underlying tissues, exacerbating resorption rate of the ridges. Hence, to address this issue of decreased prosthesis weight, hollow dentures can be fabricated. This article describes rehabilitation of compromised ridges using a simplified technique of fabricating hollow maxillary denture using glycerine soap, window impression technique for flabby anterior maxillary ridge and admix technique and neutral zone concept for registration of neutral zone in atrophic mandibular ridge.